Clinical and Radiographic Outcomes After Arthroscopic Inlay Bristow Surgery With Screw Versus Suture Button Fixation: A Comparative Study of 117 Patients With 3.3-Year Follow-up. Issue 3 (3rd March 2022) - Song, Qingfa; Zhang, Shuhan; Cheng, Xu; Xiao, Jian; Lin, Lin; Liu, Qiang; Shao, Zhenxing; Cui, Guoqing
Background: Some studies have advocated the use of suture button fixation during Bristow-Latarjet surgery to reduce complications associated with screw fixation. However, data comparing these fixation methods are relatively incomplete. Purpose: To investigate the efficacy of modified arthroscopic Bristow-Latarjet surgery and compare the clinical and radiographic outcomes using screw versus suture button fixation. Study Design: Cohort study; Level of evidence, 3. Methods: We evaluated 136 patients with traumatic anterior shoulder instability who underwent the modified arthroscopic Bristow-Latarjet surgery between June 2015 and February 2018. Of these patients, 117 who met the inclusion criteria were enrolled at a mean follow-up of 3.3 ± 0.7 years. Shoulders were separated into 2 groups based on fixation technique: screw fixation (group A; n = 63) or suture button fixation (group B; n = 54). Computed tomography imaging findings and clinical results were assessed preoperatively; immediately after operation; and postoperatively at 3 months, 6 months, 1 year, and final follow-up. Results: There were no significant differences between the groups in terms of postoperative clinical scores, the level of return to sports, range of motion, graft position, or reoperation rates. Bone healing was observed in 97.4% of the cases overall (114/117), with 98.4% bone union in group A and 96.3% in group B at final follow-up. Bone absorption was more common in group A (n = 30; 47.6%) compared with group B (n = 10; 18.5%) ( P = .003). There were no hardware-related complications in group B, compared with 7.9% of patients in group A ( P = .034). One patient in group B had a recurrent dislocation due to an unexpected event, and there were no recurrent dislocations in group A. Conclusion: After the modified arthroscopic Bristow-Latarjet procedure, both suture button and screw fixation methods demonstrated high bony healing rates and low risk of recurrence. Less coracoid graft resorption and no hardware-related complications were seen with suture button fixation.